MiR‐133a acts as a tumor suppressor in lung cancer progression by regulating the LASP1 and TGF‐β/Smad3 signaling pathway. Issue 12 (19th October 2020) - Shen, Yuyao; Yang, Yan; Li, Yahua
Abstract : Background: MiR‐133a has been confirmed to be involved in the development of multiple cancers including non‐small cell lung cancer (NSCLC). However, the precise molecular mechanism has not yet been fully elucidated. The purpose of this study was to investigate the functional role and underlying mechanism of miR‐133a in the progression of NSCLC. Methods: Quantitative real‐time PCR (qRT‐PCR) was performed to measure miR‐133a and LASP1 expression in NSCLC tissues and cells. 3‐(4, 5‐dimethyl‐2‐thiazolyl)‐2, 5‐diphenyl‐2H‐tetrazolium bromide (MTT) assay was used to detect cell viability. The protein levels were measured by western blot. The tumor growth was measured by xenograft tumor formation assay. Results: miR‐133a was significantly decreased while LASP1 was increased in NSCLC tissues and cells compared with control groups. Moreover, overexpression of miR‐133a suppressed cell viability, whereas miR‐133a knockdown enhanced the viability of A549 cells. More importantly, LASP1 was verified as a direct target of miR‐133a. Moreover, overexpression of miR‐133a inhibited the epithelial‐mesenchymal transition (EMT) and TGF‐β/Smad3 pathways by regulating LASP1 in vitro. In addition, miR‐133a mimic suppressed tumor growth by modulating the TGF‐β/Smad3 pathway in vivo. Conclusions: In conclusion, miR‐133a acted as a tumor suppressor in lung cancer progression by regulating the LASP1 and TGF‐β/Smad3 signaling pathway. Abstract : miR‐133a mimic suppressed cell viability and miR‐133a inhibitor enhanced the viability of A549 cells. LASP1 was verified as a direct target of miR‐133a. Overexpression of miR‐133a inhibited the EMT and TGF‐ß/Smad3 pathway by regulating LASP.